Tools to detect equal status for women and men in business - Artal Serrat, Margarita (Universidad Femenina del Sagrado Corazón (UNIFÉ), 2018)
The wage difficulties, the socio-labour aspects are especially difficult to reflect and that is why, in thisarticle the authors plan to introduce tools in Peruvian companies to develop actions of equality thatthey consider fundamental and that is giving satisfactory results in companies from other countries,creating a better work environment that results in an improvement of business results and impacts onthe improvement of working conditions from the perspective of gender equity.In the article there are references of how laws, social and business measures are the ones that shouldhelp tools to exist to achieve equality of opportunity between women and men in the workingenvironment. Showing the benefits of egalitarian policies and actions to prevent the brain drain, it isalso important to receive such benefits. It shows measures that are already implemented and that willhelp to make aware the Peruvian companies of the importance of introducing such tools and evaluatethem to achieve equality of opportunity within its corporate culture.